Relação entre Hipotiroidismo Subclínico e Doença Coronária: um Estudo com Angiografia - Fiarresga, A (2009)
INTRODUCTION: The definition of subclinical hypothyroidism (SH) is an asymptomatic state in which free thyroxine (T4) is normal and thyroid-stimulating hormone (TSH) levels are elevated. Its relationship with coronary disease is not clear and has been the subject of recent interest. Current evidence is conflicting and there is a lack of studies supported by coronary angiography. OBJECTIVE: To assess the relationship between SH and the presence and extent of coronary disease diagnosed by angiography. METHODS: We prospectively studied 354 consecutive patients referred for elective coronary angiography. Those with known thyroid disease, documented coronary disease or previous myocardial infarction were excluded. Fasting blood specimens were collected to measure thyroid hormones, lipid profile, high-sensitivity C-reactive protein, fibrinogen and NT-proBNP. Patients with SH were compared with those without to assess differences in clinical characteristics and biochemical and angiographic results. Significant coronary disease was defined as the presence of at least one lesion with > or = 50% luminal stenosis. Lesions with <50% stenosis were considered minimal. RESULTS: SH was diagnosed in 32 (9%) patients. Mean age was similar between the groups. There were more women (66% vs. 39%; p=0.003) and atrial fibrillation was more frequent (25% vs. 11%; p=0.016) in the group of patients with SH. There were no significant differences in the other baseline clinical parameters, and blood biochemistry results were similar in the two groups, with the exception of higher levels of NT-proBNP in SH patients, although without statistical significance. The angiographic results were as follows: significant coronary disease (SH 28.1% vs. non-SH 43.8%; p=0.087); three-vessel disease (9.4% vs. 9.9%; p=0.919); two-vessel disease (12.5% vs. 13.4%; p=0.892); single-vessel disease (6.3% vs. 29.5%; p=0.051); minimal lesions (9.4% vs. 10.9%; p=0.794); and no coronary disease (62.4% vs, 45.3%; p=0.064). CONCLUSION: In this population SH was not associated with the presence or extent of coronary disease diagnosed by coronary angiography.